Autophagic degradation of claudin‐5 mediated by its binding to a Clostridium perfringens enterotoxin fragment modulates endothelial barrier permeability. Issue 7 (21st February 2022) - Lin, Panpan; Tan, Rongbang; Yu, Ping; Li, Yanyu; Mo, Yuqian; Li, Wen; Zhang, Jingjing
Abstract : The blood‐brain barrier (BBB) protects the central nervous system (CNS) from harmful elements, while it also restricts efficient drug delivery into the CNS. Previously, we generated a mutated fragment of Clostridium perfringens enterotoxin (cCPEYWSH ) which specifically binds to the endothelial tight junction protein claudin‐5. Here, we explore the mechanisms regulating the dynamics of membranous claudin‐5 and BBB permeability. Following cCPEYWSH binding to claudin‐5, caveolin‐1 mediates the redistribution of claudin‐5 to the cytosol. This abnormal cytosolic aggregation triggers the autophagic degradation of claudin‐5, leading to an increase in BBB permeability. Enhancement or inhibition of autophagy accelerates or inhibits the degradation of cytosolic claudin‐5, respectively. Our findings may pave the way for improving BBB permeability for drug delivery. Abstract : This study explores the mechanisms regulating the dynamics of the endothelial tight junction protein claudin‐5 and blood‐brain barrier permeability following specific binding of a mutated fragment of Clostridium perfringens enterotoxin (cCPEYWSH ) and claudin‐5. Upon binding of cCPEYWSH to claudin‐5, caveolin‐1 mediates the redistribution of membranous claudin‐5 to the cytosol. The autolysosomal pathway is then activated to degrade the cytosolic aggregates including claudin‐5. The removal of claudin‐5 causes a temporary opening of the blood‐brain barrier.